NOD-like receptors in asthma - Alvarez-Simon, Daniel; Ait Yahia, Saliha; de Nadai, Patricia; Audousset, Camille; Chamaillard, Mathias; Boneca, Ivo Gomperts; Tsicopoulos, Anne (Frontiers in Immunology, 2022)
Asthma is an extremely prevalent chronic inflammatory disease of the airway where innate and adaptive immune systems participate collectively with epithelial and other structural cells to cause airway hyperresponsiveness, mucus overproduction, airway narrowing, and remodeling. The nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) are a family of intracellular innate immune sensors that detect microbe-associated molecular patterns and damage-associated molecular patterns, well-recognized for their central roles in the maintenance of tissue homeostasis and host defense against bacteria, viruses and fungi. In recent times, NLRs have been increasingly acknowledged as much more than innate sensors and have emerged also as relevant players in diseases classically defined by their adaptive immune responses such as asthma. In this review article, we discuss the current knowledge and recent developments about NLR expression, activation and function in relation to asthma and examine the potential interventions in NLR signaling as asthma immunomodulatory therapies.